KEGIATAN SENAM MAUMERE UNTUK MELANCARKAN PEREDARAN DARAH PADA LANJUT USIA - Purhadi; Suryani; Ida Ayu Gede Wahyu Wedanthi; Putri Kusuma Handayani; Muhammad Febrian Rouf; Amalita Puji Anggitasari; Setyaningsih (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2023)
Background: The majority of Krangganharjo Village residents work as farmers, and the area is mostly rice fields. Health problems such as hypertension, diabetes mellitus and gout often occur in people aged 55 years and over. Even though health facilities are good, the public's willingness to participate in health activities such as posyandu (Posyandu) or health checks is still low.   Method: This activity aims to examine the impact of Maumere dance exercises on hypertension in elderly residents in Krangganharjo Village. Activity   Results: The results of the activity showed a significant increase in participants' knowledge about hypertension and Maumere dance after the intervention. In addition, the participants showed a significant reduction in blood pressure after the Maumere dance practice.   Conclusion: From this activity it can be concluded that community service activities such as education, blood pressure measurement, and the Maumere dance can effectively reduce hypertension in the elderly population. Thus the importance of physical activity, such as Maumere dance, in improving heart health and reducing hypertension.